Einfluss der Korngröße auf ferroelektrische Eigenschaften dotierter Pb(Zr1-xTix)O3 Materialien - Picht, Gunnar (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2013)
In the present study, the grain size of various PZT ceramics was varied in a range between 300 nm and 10 microns to study their dielectric, piezoelectric and electromechanical behaviour. The performed microstructural analyzes and crystal structure studies show a significant impact of the grain size on the ferroelectric domain size and structure. As a result of this study a model for the influence of grain size on the properties of the PZT ceramics could be derived.